THE IMPACT OF ACCOUNTING INFORMATION SYSTEM ON THE ISLAMIC BANKS OF JORDAN: AN EMPIRICAL STUDY - Abdallah Alrabei, Ali Mahmoud (European Scientific Journal, ESJ, 2014)
The aim of this paper is to evaluate the impact of Accounting Information System in the Jordanian Islamic banks. The most important results that banks rely on accounting systems, by connecting all the banking services of banks each department separately and linking between all departments at the same time, dependence on accounting information systems to satisfy the clients through the implementation of banking clients as quickly and with minimal effort. In order to realize the research objectives, a questionnaire was designed and distributed to the financial managers, accountants, interior auditors and heads of accounting departments in Islamic banks of Jordan. A total of 42 questionnaires were distributed and 35 were received back which equals to (83.33%) which is considered good and acceptable. The results were analysed by using SPSS and other statistical methods. The results showed that the Accounting Information System (AISs) are most common in the Jordanian Islamic banks and it helps in providing appropriate information about available substances at the right time. Finally some conclusions and suggestions for further research are discussed.